INFLUENCE OF ENTREPRENEURIAL SKILLS AND INNOVATION ON PERFORMANCE OF SMALL AND MEDIUM ENTERPRISES (SMEs) REVIEW FROM THEORETICAL LITERATURE - Nyikuri, Jane Matingi; Nduta, R. Winnifred; Mutua, Jemmy (Machakos University, 2019)
The Small and Medium Enterprises (SMES) sector plays an increasingly important role in many economies in the world. Innovation is an important issue for many SMEs. Entrepreneurial skills as the skills needed to develop innovative products and services and to generate solutions to emerging needs in the marketplace. Innovation is the creation of a of new products and services in all sectors of the economy, new marketing methods and changes in ways of organizing businesses, in their business practices, workplace organization and external relations. The entrepreneur in SMEs is often engaged in promoting novel products and in relating to relevant clients and partners through effective communication processes and instruments such as word of mouth and personal networking. The secondary data collected was analyzed using descriptive statistics and quantitatively. The data was presented through report writing.The study found out that small medium enterprises have introduced more innovative products and services, have developed and implemented new business methods and services which have improved productions and delivery of services and that innovative marketing and promotion campaigns to find new markets have had significant implication on financial performance of SMEs. There is need for the government to foster innovation amongst SMEs through creation of a business environment conducive for entrepreneurship, creation of awareness and implementation of relevant policies. In terms of improving process innovation SMEs need to focus on improving their core competences. SMEs need to pursue market innovation strategies that focus on product customization and customer intimacy in delivering their products and services.
Keywords: Entrepreneurial skills; Innovation; Performance; SMEs